Cofilin is correlated with sperm quality and influences sperm fertilizing capacity in humans. (1st July 2016) - Chen, S. M.; Chen, X. M.; Lu, Y. L.; Liu, B.; Jiang, M.; Ma, Y. X.
Summary: Spermatozoa should undergo a series of biochemical modifications in female reproduction tract, which is collectively called sperm capacitation. The capacitated spermatozoa can bind to the egg zona pellucida, resulting in the occurrence of acrosome reaction which enabled spermatozoa penetrate into the egg. The formation of actin plays an important role in these processes. Actin polymerized during sperm capacitation, but the polymers dispersed before acrosome reaction. In this study, we take our focus on actin‐binding protein, cofilin. Our results showed that the % and intensity of sperm expressing cofilin in normal sperm were significantly higher than in abnormal sperm, and the sperm expressing cofilin was correlated with sperm quality. Furthermore, treatment with anti‐cofilin antibody increased the percentage of sperm capacitation and inhibited progesterone‐ or A23187‐ induced acrosome reaction in a dose‐dependent manner. The presence of 100 ng/mL anti‐cofilin antibodies markedly blocked the sperm penetration of zona‐free hamster eggs. Besides, immunofluorescence results revealed that cofilin was colocalized with F‐actin in the midpiece of spermatozoa; however, phospho‐cofilin was expressed in the tail rather than in the midpiece of spermatozoa, which was not colocalized with F‐actin in spermatozoa. Moreover, western blot revealed that phospho‐cofilin increased in sperm capacitation, and the total cofilin and cofilin in insoluble fraction increased in acrosome reaction; immunofluorescence results showed that the amount of cofilin in acrosome increased in sperm capacitation. In conclusion, our study revealed that cofilin expression in human sperm is correlated with sperm quality and the alterations of cofilin and phospho‐cofilin in fertilization affects sperm capacitation, acrosome reaction, and spermatozoa–oocyte fusion.